The impact of next-generation sequencing on the diagnosis of pediatric-onset hereditary spastic paraplegias: new genotype-phenotype correlations for rare HSP-related genes - Travaglini, Lorena; Aiello, Chiara; Stregapede, Fabrizia; D’Amico, Adele; Alesi, Viola; Ciolfi, Andrea; Bruselles, Alessandro; Catteruccia, Michela; Pizzi, Simone; Zanni, Ginevra; Loddo, Sara; Barresi, Sabina; et al. (Neurogenetics, 2018)
Hereditary spastic paraplegias (HSP) are clinical and genetic heterogeneous diseases with more than 80 disease genes identified thus far. Studies on large cohorts of HSP patients showed that, by means of current technologies, the percentage of genetically solved cases is close to 50%. Notably, the percentage of molecularly confirmed diagnoses decreases significantly in sporadic patients. To describe our diagnostic molecular genetic approach on patients with pediatric-onset pure and complex HSP, 47 subjects with HSP underwent molecular screening of 113 known and candidate disease genes by targeted capture and massively parallel sequencing. Negative cases were successively analyzed by multiplex ligation-dependent probe amplification (MLPA) analysis for the SPAST gene and high-resolution SNP array analysis for genome-wide CNV detection. Diagnosis was molecularly confirmed in 29 out of 47 (62%) patients, most of whom had clinical diagnosis of cHSP. Although SPG11 and SPG4 remain the most frequent cause of, respectively, complex and pure HSP, a large number of pathogenic variants were disclosed in POLR3A , FA2H , DDHD2 , ATP2B4 , ENTPD1 , ERLIN2 , CAPN1 , ALS2 , ADAR1 , RNASEH2B , TUBB4A , ATL1 , and KIF1A . In a subset of these disease genes, phenotypic expansion and novel genotype-phenotype correlations were recognized. Notably, SNP array analysis did not provide any significant contribution in increasing the diagnostic yield. Our findings document the high diagnostic yield of targeted sequencing for patients with pediatric-onset, complex, and pure HSP. MLPA for SPAST and SNP array should be limited to properly selected cases based on clinical suspicion.